Analisis Hubungan Industrial pada PT. Majesty Enerbion Nusantara - Tiffanny Tiffanny; Evi Silvana Muchsinati (Lembaga Pengembangan Kinerja Dosen, 2025)
This internship report examines the issue of attendance non-compliance among sales employees at PT. Majesty Enerbion Nusantara (PT MEN) and the efforts to improve it through the implementation of a reward and punishment–based system. The main issues identified include inconsistent attendance records, inaccurate presence data, weak supervision, and irregular clock-in and clock-out times. Through field observations, interviews, and analysis of attendance documents, a comprehensive understanding of the underlying causes of non-compliance was obtained. Based on these findings, a new attendance Standard Operating Procedure (SOP), workflow flowchart, and field attendance form were designed as supporting solutions. Implementation was carried out through procedure socialization, pilot testing of the reward and punishment system, and evaluation of data before and after implementation. The results show a significant improvement in punctuality, attendance consistency, and data accuracy, with all sales employees achieving 100% compliance during the evaluation period. This program has proven effective in strengthening work discipline, enhancing HR administrative efficiency, and improving the company’s overall industrial relations quality.